Analysis on the Effect of Radiofrequency Ablation and Electrocautery in the Treatment of Vaginal Intraepithelial Neoplasia. (6th February 2023) - Xiong, Jia-Wei; Lin, Zhi-Xin; He, Liu; Zhang, Yan-Hua; Zeng, Gui-Chan; Gui, Qing-Hua
Abstract : Objective . This research intends to investigate the clinical efficacy of radiofrequency ablation and electrocautery in treating grade I or II vaginal intraepithelial neoplasia (VaIN). Methods . This is a single-center retrospective study, which collected the clinical data of 100 patients with VaIN diagnosed by colposcopy and pathological biopsy in the Gynecology and Cervical Center of Xiangzhu Branch of the Maternal and Child Health Hospital of Guangxi Zhuang Autonomous Region between January 2020 and June 2021. Patients were divided into the study group (radiofrequency ablation treatment) and the control group (electrocautery) according to differences in treatment approaches. 6- and 12-month follow-ups were performed on all patients. Gynecological examination results, liquid-based thin-layer cytology (TCT), negative conversion of human papillomavirus (HPV), curative effects, and prognosis were recorded. Results . All patients completed regular follow-ups that lasted for 6 and 12 months. The 6- and 12-month cure rates of the study group were 76.0% and 92.0%, respectively, and the data in the control group were 70.0% and 82.0%, respectively. In terms of the 6- and 12-month negative conversion rates of HPV, the data in the study group were 68.0% and 78.0%, versus 60% and 68% in the control group, respectively. The lesion duration rate showed no statistical significance between the study group (8.0%) and the control group (P  > 0.05). The analysis of postoperative follow-up complications revealed that the study group had a statistically lower overall incidence of vaginal bleeding, excessive vaginal discharge, vaginal burning sensation, and decreased vaginal elasticity than the control group (8.0% vs. 24.0% P  < 0.05). Conclusion . Both radiofrequency ablation and electrocautery have obvious clinical effects in patients with grade I or II VaIN, but the former contributed to fewer operative complications and a good prognosis, which deserves clinical promotion.